2022
DOI: 10.1016/j.msard.2021.103399
|View full text |Cite
|
Sign up to set email alerts
|

The Turkish experience of COVID-19 infection in people with NMOSD and MOGAD: A milder course?

Abstract: Background COVID-19 is a multisystemic infection with variables consequences depending on individual and comorbid conditions. The course and outcomes of COVID-19 during neuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody-associated disorders (MOGAD) are not clearly known. Objective/methods The aim of this study was to examine the features and outcomes of COVID-19 infection in NMOSD and MOGAD patients. The patients' demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…One Turkish multicenter study with 63 COVID-19 cases included patients with MOGAD in the analysis analogous to our study. 34 They described more similar outcomes (hospitalization: 22%; intensive care admission: 2%), which might indicate a milder course of COVID-19 in MOGAD but should be verified in larger studies. Owing to demographic and clinical differences, direct comparison again is not possible.…”
Section: Discussionmentioning
confidence: 85%
“…One Turkish multicenter study with 63 COVID-19 cases included patients with MOGAD in the analysis analogous to our study. 34 They described more similar outcomes (hospitalization: 22%; intensive care admission: 2%), which might indicate a milder course of COVID-19 in MOGAD but should be verified in larger studies. Owing to demographic and clinical differences, direct comparison again is not possible.…”
Section: Discussionmentioning
confidence: 85%
“…90 A Turkish registry found that only 2 out of 13 MOGAD patients had moderate/severe/ critical COVID-19, while most had mild disease, and there were no deaths reported. 91 There have been very few published cases of patients with existing MOGAD having relapses following COVID-19, though in one reported case, a relapse following mild COVID-19 symptoms correlated with serologic reappearance of anti-MOG antibody. 92…”
Section: Mogadmentioning
confidence: 94%
“…There was no difference in the hospitalization rate based on DMT use in this group. 91 In a Latin American registry of 16 NMOSD patients, 9 (56%) required hospitalization, and 5 (32%) died from COVID-19. 94 Though there are limited data on the risk of NMOSD relapse after COVID-19 infection, small studies suggest an increased risk.…”
Section: Nmosdmentioning
confidence: 99%
See 2 more Smart Citations